Pathways: a school-based, randomized controlled trial for the prevention of obesity in American Indian schoolchildren - Caballero, Benjamin (Am J Clin Nutr, 2003)
BACKGROUND: Childhood obesity is a major public health problem in the United States, particularly among American Indian communities. OBJECTIVE: The objective was to evaluate the effectiveness of a school-based, multicomponent intervention for reducing percentage body fat in American Indian schoolchildren. DESIGN: This study was a randomized, controlled, school-based trial involving 1704 children in 41 schools and was conducted over 3 consecutive years, from 3rd to 5th grades, in schools serving American Indian communities in Arizona, New Mexico, and South Dakota. The intervention had 4 components: 1) change in dietary intake, 2) increase in physical activity, 3) a classroom curriculum focused on healthy eating and lifestyle, and 4) a family-involvement program. The main outcome was percentage body fat; other outcomes included dietary intake, physical activity, and knowledge, attitudes, and behaviors. RESULTS: The intervention resulted in no significant reduction in percentage body fat. However, a significant reduction in the percentage of energy from fat was observed in the intervention schools. Total energy intake (by 24-h dietary recall) was significantly reduced in the intervention schools but energy intake (by direct observation) was not. Motion sensor data showed similar activity levels in both the intervention and control schools. Several components of knowledge, attitudes, and behaviors were also positively and significantly changed by the intervention. CONCLUSIONS: These results document the feasibility of implementing a multicomponent program for obesity prevention in elementary schools serving American Indian communities. The program produced significant positive changes in fat intake and in food- and health-related knowledge and behaviors. More intense or longer interventions may be needed to significantly reduce adiposity in this population.